Rancang Bangun Rangkaian Digital Programable Counter - Aisyah Khoirun Nisa (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
In this era where the development of digital technology is increasingly sophisticated, because of the role of the flip-flop which can display its function as the basis of a counter. The counter circuit is a combination of combinational and sequential circuits consisting of basic logic gates, flip-flops and other ICs. This research uses experimental methods to design, build and test the performance of the counter circuit system directly. The main components used include IC, seven segment display and sensors. The design is carried out by creating a truth table to ensure the desired constraints on the circuit being created, circuit schematic and PCB layout. The research results show that the designed counter circuit can count up to 256 and will reset to 000 after reaching that limit.